Precision Livestock Farming: Precision feeding technologies and sustainable livestock production - Banhazi, T M; Babinszky, L; Halas, V; Tscharke, M (International Journal of Agricultural and Biological Engineering, 2012)
In order to be able to produce safe, uniform, cheap, environmentally- and welfare-friendly food products and market these products in an increasingly complex international agricultural market, livestock producers must have access to timely production related information. Especially the information related to feeding/nutritional issues is important, as feeding related costs are always significant part of variables costs for all types of livestock production. Therefore, automating the collection, analysis and use of production related information on livestock farms will be essential for improving livestock productivity in the future. Electronically-controlled livestock production systems with an information and communication technology (ICT) focus are required to ensure that information is collected in a cost effective and timely manner and readily acted upon on farms. New electronic and ICT related technologies introduced on farms as part of Precision Livestock Farming (PLF) systems will facilitate livestock management methods that are more responsive to market signals. The PLF technologies encompass methods for electronically measuring the critical components of the production system that indicate the efficiency of resource use, interpreting the information captured and controlling processes to ensure optimum efficiency of both resource use and livestock productivity. These envisaged real-time monitoring and control systems could dramatically improve production efficiency of livestock enterprises. However, further research and development is required, as some of the components of PLF systems are in different stages of development. In addition, an overall strategy for the adoption and commercial exploitation of PLF systems needs to be developed in collaboration with private companies. This article outlines the potential role PLF can play in ensuring that the best possible management processes are implemented on farms to improve farm profitability, quality of products, welfare of livestock and sustainability of the farm environment, especially as it related to intensive livestock species.